The Improvement in Exercise Performance during Reduced Muscle Mass Exercise is Associated with an Increase in Femoral Blood Flow in Older and Younger Endurance-Trained Athletes - Haddad, Toni; Spence, Angela; Peiffer, Jeremiah; Blain, Gregory; Abbiss, Chris (University of Uludag, 2024)
This study investigated whether the improved performance observed with maximal self-paced single-leg (SL), compared with double-leg (DL) cycling, is associated with enhanced femoral blood flow and/or altered tissue oxygenation. The hyperaemic response to exercise was assessed in younger and older athletes. Power output was measured in 12 older (65 ± 4 y) and 12 younger (35 ± 5 y) endurance-trained individuals performing 2 x 3 min maximal self-paced exercise using SL and DL cycling. Blood flow (BF) in the femoral artery was assessed using Doppler ultrasound and muscle oxygenation was measured using near-infrared spectroscopy on the vastus lateralis. SL cycling elicited a greater power output (295 ± 83 vs 265 ± 70 W, P < 0.001) and peak femoral BF (1749.1 ± 533.3 vs 1329.7 ± 391.7 ml/min, P < 0.001) compared with DL cycling. Older individuals had a lower peak BF in response to exercise (1355.4 ± 385.8 vs 1765.2 ± 559.6 ml/min, P = 0.019) compared with younger individuals. Peak BF in response to exercise was correlated with power output during SL (r = 0.655, P = 0.002) and DL (r = 0.666, P = 0.001) cycling. The greater exercise performance during SL compared with DL cycling may be partly explained by a greater hyperaemic response when reducing active muscle mass. Despite regular endurance training, older athletes had a lower femoral BF in response to maximal self-paced exercise compared with younger athletes.